Factors influencing the choice of market channels among cashew nut farmers in Mtwara rural district, Tanzania - Olivia Severine Kasabago; Joseph Magali; Mato Magobe (Journal of Management Small and Medium Enterprises (SMEs), 2026)
The cashew nut industry is one of the major agricultural sectors whose performance, through effective policies, can lead to increased economic development and improved welfare for Tanzanian farmers. The study assessed the factors influencing cashew nut production in Mtwara Rural District. Specifically, the study intended to examine the effects of demographic characteristics, market constraints, and institutional arrangements on market channel choice. A structured questionnaire was used to recruit 397 respondents through simple random sampling. Data were analyzed using descriptive and ordinary logistic regression methods. Results revealed that education level, gender, and alternative income sources were major drivers of farmers' market channel choice. Secondary education significantly increased the likelihood of formal market participation. In contrast, male farmers and those with other sources of income relied more on informal channels. Likewise, dealing with market constraints and institutional barriers positively influenced the choice of an informal cashew nuts market channel. The study concludes that policymakers and other actors should work collaboratively to improve the cashew nut marketing channel. Keywords : Market Channels; Logistic Regression; Demographic Factors; Market Constraints; Institutional Barriers